Doing qualitative research differently a psychosocial approach - Hollway, Wendy; Jefferson, Tony 1946- (SAGE, 2013)
"Wendy Hollway and Tony Jefferson have updated their ground-breaking book for students and researchers looking to do qualitative research differently. The new edition critically reviews many of the assumptions, claims and methods of qualitative research and also acts as a 'how to' guide to the method the authors call the Free Association Narrative Interview. In the new edition, the authors situate their arguments firmly within a tradition of psychosocial research and show how their method has developed over the last decade. The book follows this approach through the phases of empirical research practice. At each stage they use examples from their own research and end with an extended case study which demonstrates the value of their method in producing a psychosocial research subject; that is, one with socially-imbued depth, complexity and biographical uniqueness."--Publisher's website